Detection of FOXP-3 Expression in a Sample of Iraqi Cervical Cancer Patients Using Immunohistochemistry Technique - Al-Zwaini, Yasser kadhim Hashem; Al-Mugdadi, Suhad Faisal Hatem; Abbas, Wassan Abdul Kareem (Iraqi Journal of Science, 2022)
This paper aims to find out if FOXP-3 was expressed in samples from Iraqi cervical cancer patients. Expression of FOXP-3 was detected in 55 cervical tissue samples by immunohistochemistry. Since thirty-five cases of aggressive cervical cancer were included, along with 20 normal samples used as controls. The nucleus and cytoplasm levels of FOXP-3 were counted, considering the ratio of positive cells and intensity. FOXP3 cytoplasmic staining was found in 27 out of 35 cases. Only 11 out of 35 samples displayed nuclear lymphocyte staining. Furthermore, four samples expressed this marker in both the nuclear and cytoplasm of the cervical cells. There is a highly significant difference in FOXP3 expression in the cytoplasm of malignant cells and lymphocytes compared to normal samples. Seven samples out of 11 cells correlated with lymph vascular invasion. These results show that tissue positive FOXP-3 possesses a possible diagnostic marker for Iraqi cervical cancer. FOXP3 is significantly expressed in cancer cells, and lymphocyte infiltrates [T-reg] compared to normal.